An Investigation Of The Relationship Between Studentsâ€™ Views On Homework And Their Learning Styles - Saban, Ayten Iflazoglu (European Scientific Journal, ESJ, 2016)
The purpose of this study is to identify the relationship between studentsâ€™ views on homework and their learning styles. The study follows a descriptive survey model. It is also an example of descriptive study in relational screening model. Target population is all first, second, third, and fourth year students who are enrolled in Ã‡ukurova University Primary School Classroom Teaching Department. The participants are 443 students who volunteered to fill in the data collection forms used in the study. Of the participants, 90 were first year, 103 were second year, 140 were third year, and 110 were fourth year students. 275 of the students participating in the study were female (62.1%) and 168 were male (37.9%). The data were collected through â€œHomework Attitudes Scaleâ€ developed by GÃ¼ndÃ¼z (2005), Kolbâ€™s Learning Styles Inventory (LSI) which was first examined for its applicability in Turkey by AÅŸkar and Akkoyunlu (1993), â€œHomework Purpose Scaleâ€, â€œHomework Management Scaleâ€ and â€œPersonal Information Formâ€ developed by the researcher. No instruments were used to measure studentsâ€™ academic success levels; their academic success was identified according to the overall mean score obtained from the scores they received from all lessons. Findings show that 141 students (31.8%) preferred assimilating learning style while 133 students (30%) preferred converging learning style. Dominant learning style was found to differ according to grade level and grade point average. The difference in terms of homework attitudes, homework purpose, and homework management scale mean scores was in favour of mostly students who have converging learning style. Besides, there was a significant difference in terms of doing homework on time in favour of students who have converging learning style, and there was a significant difference in terms of coming to class without homework in favour of students who have diverging learning style.